A review of current state-level adverse medical event reporting practices : toward national standards - Beckett, Megan K. (Technical report (Rand Corporation) ;, 2006)
Nearly half of states require or request the reporting of adverse medical events. In 2003, the Institute of Medicine (Patient Safety: Achieving a New Standard of Care) called for the use of consistent standards for medical error reporting. Standardization will facilitate the creation of a national patient safety repository that aggregates data from states and enable policymakers to track trends in adverse events nationally. The Agency for Healthcare Research and Quality (AHRQ) is leading the national Patient Safety Initiative to combat medical errors. This report summarizes the results of an AHRQ sponsored 50-state survey of adverse reporting systems in 2004. It documents the consistency of information that states are collecting as part of their reporting systems, identifies issues related to establishing a national patient safety repository, and presents an action plan to implement a standardized nationwide system elicited from an external advisory panel that was convened explicitly for this purpose.